RANCANG BANGUN APLIKASI AUGMENTED REALITY UNTUK MENINGKATKAN POTENSI PENGALAMAN PENGUNJUNG BERBASIS ANDROID - Subandi, Dipa; Sujadi, Harun (Universitas Majalengka, 2025)
The Lembah Cisaar Museum in Sumedang, West Java, which exhibits ancient animal fossils, faces challenges in attracting visitors due to limited interactivity and less engaging presentation methods. This study aims to improve the visitor experience through the development of an Android-based Augmented Reality (AR) application. The research employs the Multimedia Development Life Cycle (MDLC) method, consisting of concept, design, material collecting, assembly, testing, and distribution, combined with usability testing. The developed application integrates 3D fossil visualizations, interactive markers, and voice-over narration using Unity, Blender, and Vuforia. Usability testing involving 40 respondents indicated that 89% of users found the application engaging, 91% reported increased interest in visiting the museum, and 92% considered the information beneficial. These findings demonstrate that AR technology can significantly enhance educational value, interactivity, and visitor engagement. The implementation of this AR application provides a modern digital solution to introduce cultural heritage, supporting the transformation of museums into accessible and technology-based educational platforms